Strukturel semantik og formel leksikalsk repræsentation - Feil, Ruth M.E.; Laursen, Bo (HERMES - Journal of Language and Communication in Business, 1989)
This paper deals with lexical semantics from a European structuralist point of view. Three fundamentals of the tradition are treated: 1) ’meaning’ viewed as ’sense’ and not ’reference’, 2) the semantic interdependence between words, and 3) componential analysis of lexical meaning. The structuralist approach to lexical semantics is commented upon with respect to its adequacy as a theory for the description of word meaning and to its explicitness in view of a formal representation of word meaning.